A rare association of central hypothyroidism and adrenal insufficiency in a boy with Williams-Beuren syndrome - Devi Dayal; Dinesh Giri; Senthil Senniappan (Korean Society of Pediatric Endocrinology, 2017)
Primary hypothyroidism related to morphological and volumetric abnormalities of the thyroid gland is one of the commonest of several endocrine dysfunctions in Williams-Beuren syndrome (WBS). We report a 10-month-old boy with WBS who presented with central hypothyroidism. During the neonatal period, he had prolonged jaundice, feeding difficulties and episodes of colic that continued during early infancy. Additionally, there was slowing of growth and mild developmental delay. He underwent surgical repair for supravalvular aortic stenosis at 6 months of age. An evaluation done to exclude cortisol deficiency before initiating levothyroxine lead to the detection of secondary adrenal insufficiency, unreported previously in WBS. In addition, insulin-like growth factor-1 (IGF-1) and IGF-binding protein-3 levels were low. This report of hypopituitarism in WBS indicates a need for complete evaluation of pituitary dysfunction in children with WBS.